Respuesta :

Answer:

(x + 9)(5x - 1)

Step-by-step explanation:

Given

5x² + 44x - 9

Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term.

product = 5 × - 9 = - 45 and sum = + 44

The factors are + 45 and - 1

Use these factors to split the x- term

5x² + 45x - x - 9 ( factor the first/second and third/fourth terms )

= 5x(x + 9) - 1(x + 9) ← factor out (x + 9) from each term

= (x + 9)(5x - 1) ← in factored form